Motivational Interviewing to Improve the Uptake of Colorectal Cancer Screening: A Systematic Review and Meta-Analysis - Long, Novia Niannian; Lau, Michele Petrova Xin Ling; Lee, Ainsley Ryan Yan Bin; Yam, Natalie Elizabeth; Koh, Nicholas Ye Kai; Ho, Cyrus Su Hui (Frontiers in Medicine, 2022)
Introduction: Colorectal cancer screening when done early can significantly reduce mortality. However, screening compliance is still lower than expected even in countries with established screening programs. Motivational interviewing is an approach that has been explored to promote behavioral change including screening compliance. This review synthesizes the efficacy of motivational interviewing in promoting uptake of colorectal screening modalities and is the only review so far that examines motivational interviewing for colorectal cancer screening alone. Methods: A systematic review and meta-analysis was conducted to examine the effects of motivational interviewing for colorectal cancer screening. PubMed, EMBASE, CENTRAL, PsycINFO and CINAHL were searched to identify eligible studies from inception to June 2021 and selection criteria was defined. Risk of bias was assessed using the Cochrane Risk of Bias 2.0 tool. The DerSimonian and Laird random effects model was used in the statistical analysis for studies included in the meta-analysis. Results: 14 studies from 14 randomized-controlled trials with a low to moderate risk of bias were analyzed. 8 studies in the systematic review showed that motivational interviewing is superior to a control group. Meta-analysis was conducted on 11 studies and showed that motivational interviewing is statistically significant in increasing colorectal cancer screening rates in both intention-to-treat and per-protocol analysis. Timing of data collection of colorectal cancer screening rates did not make a significant difference to the efficacy of motivational interviewing. Studies that offered and accepted a mixture of colorectal screening modalities such as colonoscopy and fecal immunochemical tests were significantly more likely to have favorable colorectal screening outcomes. Heterogeneity in intervention was noted between studies, specifically differences in the training of interventionists, intervention delivery and comparator components. Conclusion: Motivational interviewing is a tailored intervention demonstrating mixed evidence in improving colorectal cancer screening attendance amongst individuals. More research is needed to rigorously compare the effect of motivational interviewing alone versus in combination with other screening promotion strategies to enhance colorectal cancer screening compliance.